The Effect of Intellectual Capital on Financial Performance Before and During The COVID-19 Pandemic - Caroline Oktavia Gunawan; Kazia Laturette; Yopy Junianto (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This study aims to examine the effect of intellectual capital on the financial performance of manufacturing companies in the consumer goods sector before and during the Covid-19 period being listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. Sampling was carried out using the purposive sampling method, there were 51 companies that met the criteria, and the number of samples in the study before and during the Covid-19 period was 196 data. This study uses multiple linear regression analysis. The results showed that human capital efficiency before and during Covid-19 had a significant positive effect on financial performance, structural capital efficiency before and during Covid-19 had no effect on financial performance, and capital employed efficiency before Covid-19 had a significant effect. significantly negative and during the Covid-19 period had a significant positive effect on the financial performance of manufacturing companies in the consumer goods sector listed on the IDX for the 2018-2021 period.